2016
DOI: 10.18805/lr.v39i6.6641
|View full text |Cite
|
Sign up to set email alerts
|

Study on L-Dopa content in faba bean flowers

Abstract: Faba bean (Vicia faba L.) flower is rich in L-Dopa used for the treatment of Parkinson's disease. In order to utilize L-Dopa from faba bean flower more efficiently, the effects of factors on L-Dopa contents in faba bean flowers determined by HPLC were studied. Results showed that the L-Dopa contents in faba bean flowers differenced in germplasm resources, the highest L-Dopa content in faba bean flowers was 20 times higher than that of the lowest. The average contents of two years ranged from 0.53% to 10.63%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In the study in which the effects of factors on L-DOPA contents in faba bean were examined, Kai-Bin et al determined the average L-DOPA content in bean flowers as 4.48% [41]. In the same study, it has been reported that L-DOPA contents may vary according to flower colors, L-DOPA content decreases proportional to the darkening of the color, and the flower bud form contains more L-DOPA compared to the open flower form.…”
Section: L-dopa and Vicine Contentmentioning
confidence: 99%
“…In the study in which the effects of factors on L-DOPA contents in faba bean were examined, Kai-Bin et al determined the average L-DOPA content in bean flowers as 4.48% [41]. In the same study, it has been reported that L-DOPA contents may vary according to flower colors, L-DOPA content decreases proportional to the darkening of the color, and the flower bud form contains more L-DOPA compared to the open flower form.…”
Section: L-dopa and Vicine Contentmentioning
confidence: 99%